Effects of injected ice particles in the lower stratosphere on the Antarctic ozone hole. Issue 5 (7th May 2015) - Nagase, H.; Kinnison, D. E.; Petersen, A. K.; Vitt, F.; Brasseur, G. P.
Abstract The Antarctic ozone hole will continue to be observed in the next 35–50 years, although the emissions of chlorofluorocarbons (CFCs) have gradually been phased out during the last two decades. In this paper, we suggest a geo‐engineering approach that will remove substantial amounts of hydrogen chloride (HCl) from the lower stratosphere in fall, and hence limit the formation of the Antarctic ozone hole in late winter and early spring. HCl will be removed by ice from the atmosphere at temperatures higher than the threshold under which polar stratospheric clouds (PSCs) are formed if sufficiently large amounts of ice are supplied to produce water saturation. A detailed chemical‐climate numerical model is used to assess the expected efficiency of the proposed geo‐engineering method, and specifically to calculate the removal of HCl by ice particles. The size of ice particles appears to be a key parameter: larger particles (with a radius between 10 and 100 µm) appear to be most efficient for removing HCl. Sensitivity studies lead to the conclusions that the ozone recovery is effective when ice particles are supplied during May and June in the latitude band ranging from 70°S to 90°S and in the altitude layer ranging from 10 to 26 km. It appears, therefore, that supplying ice particles to the Antarctic lower stratosphere could be effective in reducing the depth of the ozone hole. In addition, photodegradation of CFCs might be accelerated when ice is supplied due to enhanced vertical transport of this efficient greenhouse gas.